2016
DOI: 10.1007/s10750-016-2888-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the Asian clam species complex (Corbicula) invasion in the Iberian Peninsula

Abstract: The Asian clam (Corbicula sp.) is an invasive freshwater bivalve native to Asia, the Middle East, Australia, and Africa. It is now widely distributed around the world producing large ecological and economic impacts. Three well-described invasive lineages form a cryptic species complex with asexual reproduction based on androgenesis. In this study, we collected 175 individuals from different Iberian, European, and North American locations to genetically study Corbicula invasion in the Iberian Peninsula using CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 39 publications
(124 reference statements)
3
36
1
Order By: Relevance
“…We also found that both the invasive and native androgenetic Corbicula individuals are mostly heterozygotes 411 (also confirmed by Pigneur et al, 2014;Peñarrubia et al 2017). Hybridization or nuclear genetic capture events 412 between lineages, which are more likely to occur in asexual organisms that retained sexual features (such as 413 androgens where fertilization occurs, Figure 1), might facilitate the evolution of genetic diversity, enhanced 414 heterozygosity and the occurrence of distinct alleles from different genetic lineages within one individual.…”
Section: Genetic Captures Among Corbicula Lineages 378supporting
confidence: 65%
See 2 more Smart Citations
“…We also found that both the invasive and native androgenetic Corbicula individuals are mostly heterozygotes 411 (also confirmed by Pigneur et al, 2014;Peñarrubia et al 2017). Hybridization or nuclear genetic capture events 412 between lineages, which are more likely to occur in asexual organisms that retained sexual features (such as 413 androgens where fertilization occurs, Figure 1), might facilitate the evolution of genetic diversity, enhanced 414 heterozygosity and the occurrence of distinct alleles from different genetic lineages within one individual.…”
Section: Genetic Captures Among Corbicula Lineages 378supporting
confidence: 65%
“…These invasive forms appear to exhibit virtually no genetic diversity over their invasive range at all the 74 nuclear and mitochondrial markers tested (Hedtke et al, 2008;Pigneur et al, 2014;Gomes et al, 2016), and seem 75 to possess only four, unique mitochondrial COI haplotypes (Pigneur et al, 2012(Pigneur et al, , 2014: haplotype FW5 (form 76 A/R), haplotype FW17 (form C/S), haplotype FW1 (form B) and haplotype FW4 (form Rlc). As the latter two 77 only differ at one SNP in COI, they were referred to as RlcB by Peñarrubia et al, 2017; however, we still 78 distinguish these two forms in our present work because of their very distinct microsatellite genotypes and their 79 different morphologies (Pigneur et al 2014). When distinct invasive lineages are found in sympatry, cytonuclear 80 mismatches and hybrids are often detected ( In contrast, androgenetic Corbicula from Lake Biwa in Japan (native area) are characterized by a high genetic 89…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Asexual Corbicula lineages have been invading freshwater ecosystems across the globe for almost a century and are considered a major aquatic pest (summarized by Tiemann et al, 2017). Their first documented appearance outside of their native range occurred in western North America in the 1920s (summarized by Lee et al, 2005; Tiemann et al, 2017) and since then they have reportedly spread throughout North and much of South America (Beasley, Tagliaro & Figueiredo, 2003; Lee et al, 2005) and across Europe (Pigneur et al, 2011, 2014; Crespo et al, 2015; Peñarrubia et al, 2017), with Antarctica being the only continent with no known occurrences (Crespo et al, 2015; GBIF.org, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the phylogenetic relationships among the invasive clonal lineages worldwide are poorly supported in both nuclear and mt datasets (Lee et al, 2005; Hedtke et al, 2008; Hedtke, Glaubrecht & Hillis, 2011; Pigneur et al, 2012, 2014). There is evidence of hybridization between forms with heterozygous genotypes found in some specimens, e.g., heterozygous sequences were documented for nuclear 28S genotypes between clonal lineages B and C from Iguazu Falls in South America (Lee et al, 2005), Forms A and C in the Ebro River delta, Spain (Peñarrubia et al, 2017), and between Forms R and S from Northern Russia (Bespalaya et al, 2018) and Pigneur et al (2014) found evidence of hybridization between Forms A and B in the Ohio River and between A and C in the River Seine using microsatellite loci. In addition, these asexual invasive Corbicula lineages appear capable, in at least some cases, of parasitizing the eggs of other co-occurring clones where the sperm of one clone “steals” the eggs, and thus the mitochondria, of another clone (Lee et al, 2005; Hedtke, Glaubrecht & Hillis, 2011; Pigneur et al, 2014; Tiemann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%